2009
DOI: 10.3201/eid1502.080712
|View full text |Cite
|
Sign up to set email alerts
|

Imported Malaria in Children in Industrialized Countries, 1992–2002

Abstract: Children account for an appreciable proportion of total imported malaria cases, yet few studies have quantifi ed these cases, identifi ed trends, or suggested evidence-based prevention strategies for this group of travelers. We therefore sought to identify numbers of cases and deaths, Plasmodium species, place of malaria acquisition, preventive measures used, and national origin of malaria in children. We analyzed retrospective data from Australia,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 27 publications
4
43
1
7
Order By: Relevance
“…The data also indicated that P falciparum acquired in sub-Saharan Africa was the most common infection and that VFR children accounted for a majority of cases. 2,10,18 In contrast to studies in adults, no increased risk was found for male gender. 27 Dengue fever and enteric fever were the mostfrequently identified specific causes of systemic febrile illnesses among pediatric travelers returning from tropical regions other than subSaharan Africa.…”
Section: Figurecontrasting
confidence: 49%
See 1 more Smart Citation
“…The data also indicated that P falciparum acquired in sub-Saharan Africa was the most common infection and that VFR children accounted for a majority of cases. 2,10,18 In contrast to studies in adults, no increased risk was found for male gender. 27 Dengue fever and enteric fever were the mostfrequently identified specific causes of systemic febrile illnesses among pediatric travelers returning from tropical regions other than subSaharan Africa.…”
Section: Figurecontrasting
confidence: 49%
“…17 Innovative methods to improve access to pretravel services for VFR travelers have used approaches such as communitybased programs (eg, in sports clubs, churches, or schools) and locallanguage programming through media to educate populations about risks. 18,19 Additional efforts to increase education and to decrease barriers to care are crucial.…”
Section: Figurementioning
confidence: 99%
“…4 Similarly, in a large analysis of 12,000 cases of imported pediatric malaria, the main risk areas were VFR destinations rather than tourist targets. 22 Immigrants from endemic areas may consider malaria a benign condition, but it should be noted that 26% of our cases with complicated falciparum malaria did occur in this particular subgroup of travelers. Still, only 0.06% of our VFR patients with falciparum malaria are known to have died.…”
Section: Discussionmentioning
confidence: 99%
“…Many VFRs stay in family settings in which they may encounter suboptimal housing conditions and increased malaria risk (Bacaner et al, 2004;Scolari et al, 2002;Muentener et al, 1999;Fulford and Keystone, 2005;Di Perri et al, 1994;Barnett et al, 2010;Fenner et al, 2007;Froude et al, 1992;Wagner et al, 2013). VFRs may encounter barriers such as lack of information on services, language, trust of health systems, concerns on their legal status and cost of malaria chemoprophylaxis, which may limit their access to travel clinics (Bacaner et al, 2004;Stager et al, 2009). Migrant VFRs may be exposed to risk of malaria as they visit their families in rural areas with higher malaria transmission rates (Schlagenhauf et al, 2003).…”
Section: Visiting Friends and Relativesmentioning
confidence: 98%